BIOLOGICAL IMPORTANCE AND HEALTH EFFECT OF Perilla frutescence PLANT - Mohammad Asif (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
The study was designed to study the Biological importance and nutritional benefits of Perilla frutescence plant. This plant has very high biological activities. It contains various phytoconstituents such as different phenolic compounds (like rosemarinic acids, luteolin chrysoeriol, quercetin, catcehin, apigenin, etc), vitamins, minerals etc. Perilla seeds contained 30-40% fixed oil, contained both saturated (palmitic acid 5-7%, stearic acid 1-3%), unsaturated (UFAs) or polyunsaturated (PUFAs) (oleic acid 12-22%, linoleic acid 13-20%, γ-linolenic acid 0-1%, α-linolenic acid 52-64%, icosanoic acid 0-1%) fatty acids. Perilla oil is highly unsaturated oil among the all current discovered natural vegetable oils. Whole perilla plant has many important functions on improving and accelerating human health and is effective in prevention of various diseases.Key words: Perilla frutescence, biological activities, phyto-constituents, polyphenols, polyunsatured fatty acids.